Dectin-1 expression at early period of Aspergillus fumigatus infection in rat's corneal epithelium - Che, Cheng-Ye (International Journal of Ophthalmology Press, 2013)
AIM: To investigate the expression of dendritic cell-associated C-type lectin-1(dectin-1) at the early period of Aspergillus fumigatus infection in rat's corneal epithelium. METHODS: A total of 72 Wistar rats were randomly divided into three groups: A, B and C. The right eyes were chosen as experimental eyes. Group A was control group. Rats in group B were not inoculated with Aspergillus fumigatus. Group C was taken as Aspergillus fumigatus keratitis model. Rats in group B and C (six from each group) were executed randomly at 4, 8, 16 and 24 hours after experimental model being established to assess the expression of dectin-1 mRNA through real-time PCR. Another six rats in group B and C were executed randomly at 24 hours to assess the expression of dectin-1 protein through immunohistochemistry. RESULTS: The results of real-time PCR indicated that dectin-1 mRNA expression was low in corneal epithelium of normal rats'. There was no significantly difference of dectin-1 mRNA expression in group A and B (P>0.05). The expression of Aspergillus fumigatus infected corneal epithelium increased gradually after 8 hours in group C. The synchronous expression of group A and C had significant difference (P<0.01). Immunohistochemisty discovered that dectin-1 receptor existed in normal rat's corneal epithelium. Dectin-1 protein increased after 24 hours in group C. There was a significant difference of synchronous expression in group B and C (P<0.01). CONCLUSION: Dectin-1 exists in rat's corneal epithelium and its expression significantly increases at the early period of Aspergillus fumigatus infection. Dectin-1 is a pattern recognition receptor that expresses in corneal epithelium and involves in immune response to Aspergillus fungal keratitis.